Differential conformational modulations of MreB folding upon interactions with GroEL/ES and TRiC chaperonin components - Moparthi, Satish Babu (Sci Rep, 2016)
Here, we study and compare the mechanisms of action of the GroEL/GroES and the TRiC chaperonin systems on MreB client protein variants extracted from E. coli. MreB is a homologue to actin in prokaryotes. Single-molecule fluorescence correlation spectroscopy (FCS) and time-resolved fluorescence polarization anisotropy report the binding interaction of folding MreB with GroEL, GroES and TRiC. Fluorescence resonance energy transfer (FRET) measurements on MreB variants quantified molecular distance changes occurring during conformational rearrangements within folding MreB bound to chaperonins. We observed that the MreB structure is rearranged by a binding-induced expansion mechanism in TRiC, GroEL and GroES. These results are quantitatively comparable to the structural rearrangements found during the interaction of β-actin with GroEL and TRiC, indicating that the mechanism of chaperonins is conserved during evolution. The chaperonin-bound MreB is also significantly compacted after addition of AMP-PNP for both the GroEL/ES and TRiC systems. Most importantly, our results showed that GroES may act as an unfoldase by inducing a dramatic initial expansion of MreB (even more than for GroEL) implicating a role for MreB folding, allowing us to suggest a delivery mechanism for GroES to GroEL in prokaryotes.